Get strong for women lift heavy, train hard, see results - Silver-Fagan, Alex (Dorling Kindersley Limited, 2018)
This fitness manifesto provides clear, step-by-step exercise instruction as well as easy-to-follow workout programs so you can enter the weight room with confidence and become your strongest self. Using strength-training, cardio, and weight-lifting exercises, Get Strong for Women gives you the tools you need to build muscle, burn fat, and get a strong, fit body.